(untitled) (Research, Society and Development, 2023)
The present article aims to explore the etiological understanding of depression from the perspective of Logotherapy, as well as its psychotherapeutic applicability. This psychological approach was created by Viktor E. Frankl, and its pillars are: the search for meaning in life, freedom of will and desire for meaning. Frankl was a survivor of concentration camps during the Second World War, this experience significantly influenced his view of human existence and contributed to the improvement of his approach. He describes depression from three sources: endogenous (organic causes), psychogenic (psychological causes) and noogenic (existential emptiness). Logotherapy offers a psychotherapeutic approach focused on the search for the meaning of life, helping the individual to develop values, constructive attitudes and face suffering. Therefore, with this research it is concluded that logotherapy is an effective approach in the treatment of depression considering the individual not only in the psychic and corporeal aspect, but also in the spiritual aspect and their search for achieving their purpose in life.